The Alimony Obligation of a Civil Servant and Non-Civil Servant Father towards Children Post-Divorce (The Study on Aceh Syar'iyyah Court Decision Study of 2019) - Djawas, Mursyid; Eriyanti, Nahara; Yulia, Anita; Fauzan, Faisal (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This research was motivated by two decisions of the Aceh Syar'iyah Court, namely decision Number 75/Pdt.G/2019/MS. Aceh in determining the child's sustenance after divorce, distinguished by the amount that must be given by civil servant and non-civil servant fathers. However, these two decisions are different from the provisions of the Compilation of Islamic Law (KHI), in which the Compilation of Islamic Law (KHI) does not mention the number of child support provisions. This is the focus of this research, in which two research questions were administered to answer the research inquiries First; what is the judge's consideration in determining the obligation of a civil servant and a non-civil servant father? Second; how does the Islamic law determine the obligations of a civil servant and non-civil servant father to children after a divorce from the study of the 2019 Aceh Syar'iyah Court judge’s decision? This is a library research investigating cases on strategies used by judges in solving various cases. The study reveals that the judge’s considerations in determining the level of child maintenance rights are differed between the judge’s decision Number 75/Pdt.G/2019/MS.Aceh and decision Number 70/Pdt.G/2019/MS.Aceh. The study suggests that the judge has different ways of determining the legal decision. The civil servant fathers are entitled to comply by article 8 PP No. 10 of 1983 jo. PP No. 45 of 1990, while the non-civil fathers are referred to the recommendation of the Compilation of Islamic Law (KHI), which is seen from the ability of the father. This is found to have been in compliance with the Islamic law. Therefore, according to the author, the difference in determining the level of income for children after divorce is relevant to Imam Syafi'i's opinion that income has a certain size. The rich father should pay two mud, middle-class fathers pay one and a half mud and the low-income fathers pay one mud.